1993
DOI: 10.1523/jneurosci.13-04-01676.1993
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration induced by beta-amyloid peptides in vitro: the role of peptide assembly state

Abstract: The progressive neurodegeneration of Alzheimer's disease has been hypothesized to be mediated, at least in part, by beta-amyloid protein. A relationship between the aggregation state of beta-amyloid protein and its ability to promote degeneration in vitro has been previously suggested. To evaluate this hypothesis and to define a structure-activity relationship for beta-amyloid, aggregation properties of an overlapping series of synthetic beta-amyloid peptides (beta APs) were investigated and compared with beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

63
1,064
5
5

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,417 publications
(1,137 citation statements)
references
References 45 publications
(39 reference statements)
63
1,064
5
5
Order By: Relevance
“…The experimental conditions were selected according to previous studies demonstrating that they mimic some of the pathological processes in AD brain, including the cognitive deficits (Nitta et al, 1994). This fragment is proposed to be the functional domain of A␤ responsible for its neurotoxic properties (Pike et al, 1993). In the past, the presence of A␤(25-35) in vivo was controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental conditions were selected according to previous studies demonstrating that they mimic some of the pathological processes in AD brain, including the cognitive deficits (Nitta et al, 1994). This fragment is proposed to be the functional domain of A␤ responsible for its neurotoxic properties (Pike et al, 1993). In the past, the presence of A␤(25-35) in vivo was controversial.…”
Section: Discussionmentioning
confidence: 99%
“…A critical challenge in understanding the mechanism of Aβ toxicity, and in the subsequent design of intervention strategies, has been the correlation of a particular aggregate structure or size with biological effects, especially toxicity. Initially, fibrils were reported to be toxic, and inhibition of fibril formation or disruption of fibrils was considered to be a viable strategy for inhibiting Aβ toxicity [62][63][64] . Subsequent studies, using SEC-purified protofibrils and monomers, showed that protofibrils exhibit stronger toxicity than monomeric and fibrillar Aβ 14,20,21 .…”
Section: High Molecular Weightmentioning
confidence: 99%
“…Primary cultures of dissociated cerebral cortical neurons were prepared from the brains of embryonic day 18 (E 18) rats as described previously [54]. Cell plated at 2.5 × 10 5 cells/cm 2 were cultured in poly-L-lysine coated six well plates (for western blot analysis) or on 24 well plates (for immunocytochemistry and assays for cell viability) and maintained in serum-free optimal Dulbecco's modified Eagles medium (DMEM) supplemented with B-27 components (Invitrogen, Carlsbad, CA).…”
Section: Cell Culturementioning
confidence: 99%
“…Cultures were maintained for 5-7 days before treatments. Neuronal survival was determined by trypan blue exclusion [54] or using the MTT 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay [30]. The purity of the preparations was checked occasionally using double staining with MAP-2 (for neurons) and GFAP (for astrocytes).…”
mentioning
confidence: 99%